2021
DOI: 10.1177/02633957211031799
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting norms of citizenship in times of democratic change

Abstract: Over the last two decades, scholars have investigated norms of citizenship by focussing primarily on ‘dutiful’ and ‘engaged’ norms. In the meantime, contemporary democracies have witnessed growing demands for more sustainable styles of living and increasing public support for authoritarian and populist ideas. These developments point to both a change and an expansion of conventional understandings and conceptions of what a ‘good citizen’ in a democratic polity ought to do. Specifically, they raise questions ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
4
0
3
Order By: Relevance
“…Citizenship norms are a type of injunctive norms (“norms of ought,” Cialdini & Trost, 1998) that elicit shared expectations of citizens’ role in politics (Dalton, 2008) and shape the meaning that citizens assign to participation (Bolzendahl & Coffé, 2013; van Deth, 2007). Citizenship norm research is informed by the democratic theory that enables scholars to assess forms of political participation against this background, evaluating to what extent some forms of political participation contribute to or hamper the democratic social order (Schnaudt et al, 2021).…”
Section: Changing Participation Forms Changing Citizenship Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…Citizenship norms are a type of injunctive norms (“norms of ought,” Cialdini & Trost, 1998) that elicit shared expectations of citizens’ role in politics (Dalton, 2008) and shape the meaning that citizens assign to participation (Bolzendahl & Coffé, 2013; van Deth, 2007). Citizenship norm research is informed by the democratic theory that enables scholars to assess forms of political participation against this background, evaluating to what extent some forms of political participation contribute to or hamper the democratic social order (Schnaudt et al, 2021).…”
Section: Changing Participation Forms Changing Citizenship Normsmentioning
confidence: 99%
“…While the democratic theory has typically informed citizenship norms research by providing benchmarks for assessing the viability, desirability, and efficacy of political and civic behavior as such, it does not provide instruments to register the actualization and emergence of norms. Instead of reducing citizens’ political action and interaction in social media environments to their support for predefined democratic norms (Schnaudt et al, 2021), looking at citizenship norms as communicative practices that unfold in social media environments may be more fruitful. Research has revealed that social media not only afford new tools for political communication (Bode et al, 2014; Theocharis & van Deth, 2018) but as spaces where political communication unfolds, they also enable processes of social and communicative change (Flanagin, 2020).…”
Section: Changing Participation Forms Changing Citizenship Normsmentioning
confidence: 99%
“…Debates par laba pilsoņa izpratni notiek jau tūkstošiem gadu -no Platona un Aristoteļa laikiem līdz mūsdienām tiek spriests, kādam ir jābūt labam pilsonim (pēdējos gados pat ir strauji pieaudzis ar šo tēmu saistīto akadēmisko publikāciju skaits; Shachar et al, 2020;Villalobos et al, 2021). Tomēr pēdējā laikā tiek apšaubīts, vai pētījumos izmantotie mērījumi atbilst pašreizējai situācijai (piemēram, nosakot iedzīvotāju aktivitātes/pasivitātes līmeni), un tiek ierosināts pārskatīt pētījumos izmantotos kritērijus (Dalton, 2008;Cohen et al, 2013;Bolzendahl & Coffé, 2013;Hooghe & Oser, 2015;Schnaudt et al, 2021). Iemesls ir saistīts ne tikai ar mainīgajām līdzdalības formām un aktivitāšu veidiem, bet arī ar pārmaiņām sabiedrības dienaskārtībā, piemēram, cilvēktiesību, vides aizsardzības aktualitātes pieaugumu u. c. Šajās diskusijās pilsonība tiek saprasta visbiežāk kā indivīda un valsts attiecības, kur indivīds izrāda lojalitāti pret valsti un saņem tās aizsardzību (van Deth, 2008).…”
Section: Laba Pilsoņa Izpratneunclassified
“…Analogous, eating ethical, ecological, and ‘climate-friendly’ food has become political, expressed among other things through so-called political consumerism [ 22 , 23 ]. Additionally, the individual responsibility to be considerate about the wider societal and environmental implications of consumption choices is hotly debated, highlighted, and gradually acknowledged across spheres and people [ 24 ]. This raises the question: RQ3: Can the behaviours and recommendations of central persons be ‘catalysts’ of a broader political engagement, such as boycotting and buycotting products for ethical, environmental, or other political reasons?…”
Section: Introductionmentioning
confidence: 99%